2005
DOI: 10.1042/bj20042075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that melatonin is enzymatically oxidized in a different manner than tryptophan: investigations with both indoleamine 2,3-dioxygenase and myeloperoxidase

Abstract: The catabolism of melatonin, whether naturally occurring or ingested, takes place via two pathways: ∼ 70 % can be accounted for by conjugation (sulpho-and glucurono-conjugation), and ∼ 30 % by oxidation. It is commonly thought that the interferoninduced enzyme indoleamine 2,3-dioxygenase (EC 1.13.11.42), which oxidizes tryptophan, is also responsible for the oxidation of 5-hydroxytryptamine (serotonin) and its derivative, melatonin. Using the recombinant enzyme expressed in Escherichia coli, we show in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 46 publications
1
59
0
5
Order By: Relevance
“…The reaction mechanism utilized by myeloperoxidase is intriguing because the enzyme used superoxide to oxidize melatonin. Although others have shown that myeloperoxidase uses hydrogen peroxide to oxidize melatonin to AFMK (34,39), we found that production of AFMK was much greater in the presence of superoxide. Furthermore, hydrogen peroxide was not essential for conversion of melatonin to AFMK.…”
Section: Discussionmentioning
confidence: 51%
“…The reaction mechanism utilized by myeloperoxidase is intriguing because the enzyme used superoxide to oxidize melatonin. Although others have shown that myeloperoxidase uses hydrogen peroxide to oxidize melatonin to AFMK (34,39), we found that production of AFMK was much greater in the presence of superoxide. Furthermore, hydrogen peroxide was not essential for conversion of melatonin to AFMK.…”
Section: Discussionmentioning
confidence: 51%
“…Although previous studies suggest that IDO can exhibit a peroxidase activity (24,25) and a recent study employed H 2 O 2 as a surrogate to form a compound II species (26), the possibility that IDO forms compound I and its implications for dioxygenase activity have not previously been addressed. This is likely due to the high reactivity of compound I making direct detection difficult, particularly in pseudo-peroxidases where the porphyrin radical rapidly transfers to adjacent amino acids to form protein-centered radicals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…of indole, as has been proposed for IDO oxidation of melatonin (8), but this possibility is ruled out for indole oxidation by incorporation of 18 O from H 2 18 O 2 . On the other hand, peroxidation could account for IDO-catalyzed ring opening of 3-methylindole and 2,3-dimethyl indole, neither of which incorporated 18 O from H 2 18 O 2 .…”
Section: •−mentioning
confidence: 99%
“…Notably, IDO does not catalyze oxidation of L-Trp by H 2 O 2 (4,8,9). Consequently, the reactivity of IDO with H 2 O 2 received little attention for more than 30 years.…”
mentioning
confidence: 99%